School Mathematics and miyō-pimōhtēwin - Stavrou, Stavros Georgios; Murphy, M. Shaun (Journal of the Canadian Association for Curriculum Studies, 2021)
We want mathematics to be a process of miyō-pimōhtēwin (walking in a good way). Using a narrative inquiry methodology, we share our experiences working alongside two Cree elementary school teachers and the students in their mathematics classroom. The teachers taught principles that balance kohtawān (our spiritual being) and make curriculum into a relational space. The principles invite school mathematics to be learned and taught in a way that foregrounds self-awareness, doing things properly, learning new ways, being thankful, being humble, leaving problems behind you, helping yourself and keeping trying. This paper also demonstrates a promising practice of Indigenization in the mathematics classroom by providing a contextual way in which Cree students and teachers engaged in school mathematics in relational ways.